Short caregiver interview and play observation for early screening of autism spectrum disorder: Behavior development screening for toddlers (BeDevel). Issue 7 (31st March 2021) - Bong, Guiyoung; Kim, So Yoon; Song, Da‐Yea; Kim, Jeong‐heun; Hong, Yoohwa; Yoon, Nan‐He; Sunwoo, Hyunjung; Jang, Jeong Yun; Oh, Miae; Kim, Jong Myeong; Lee, Kyung‐Sook; Jung, Seokjin; et al.
Abstract: This study validates behavior development screening for toddlers (BeDevel), which utilizes a combination of short caregiver interviews (BeDevel‐I) and semistructured play observations (BeDevel‐P). The data of 431 toddlers (male 66.2%; mean age ( SD ) = 29.11 (8.59) months; ASD, n = 201; developmental delay, n = 46; typically developing, n = 184), aged 18 42 months, were included in the validation of BeDevel. The best clinical estimate diagnosis, screening rate, validity, sensitivity, and reliability of BeDevel were determined based on data cross‐sectionally collected using BeDevel and existing diagnostic/screening instruments: autism diagnostic observation schedule (ADOS), autism diagnostic interview (ADI‐R), Vineland adaptive behavior scales‐II (VABS‐II), social response scales (SRS), sequenced language scale for infants (SELSI), Korean childhood autism rating scale (K‐CARS), and Korean social communication questionnaire (K‐SCQ). The k values of BeDevel‐I and BeDevel‐P were 0.055 0.732 and 0.291 0.752, respectively. Items related to social referencing in BeDevel‐P had a particularly high diagnostic validity ( k = 0.483 0.684). Reliabilities of BeDevel‐I and BeDevel‐P were sufficient (Cronbach's alpha = 0.86 0.88 and 0.92 0.95, respectively). BeDevel‐I and BeDevel‐P showed high sensitivity (BeDevel‐I: 85.00 89.29%; BeDevel‐P: 85.00 91.75%), specificity (BeDevel‐I: 77.55 89.55%; BeDevel‐P: 85.09 97.01%), PPV (BeDevel‐I: 70.83 88.54%; BeDevel‐P: 81.52 94.68%), and NPV (BeDevel‐I: 76.00 95.24%; BeDevel‐P: 84.62 95.45%). The agreement between the composite BeDevel score and ADOS, ADI‐R, K‐CARS, and K‐SCQ was >67.6% (range = 67.6 90.8%). Combining a short caregiver interview and direct play observation is a valid and reliable screening process. More studies on social referencing as an important early marker are needed. BeDevel can be utilized as a secondary screening instrument before diagnostic confirmation in clinical and community settings. Lay summary: BeDevel, which consists of a short caregiver interview and direct play observation, is a valid and reliable screening instrument for autism spectrum disorder (ASD). We suggest that BeDevel can be utilized as a secondary instrument before administering diagnostic assessments in clinical and community settings. More studies examining social referencing as a potential behavioral marker of ASD are needed.